Directions for research and training in plant omics: Big Questions and Big Data. (23rd April 2019) - Argueso, Cristiana T.; Assmann, Sarah M.; Birnbaum, Kenneth D.; Chen, Sixue; Dinneny, José R.; Doherty, Colleen J.; Eveland, Andrea L.; Friesner, Joanna; Greenlee, Vanessa R.; Law, Julie A.; Marshall‐Colón, Amy; Mason, Grace Alex; et al.
Abstract: A key remit of the NSF‐funded "Arabidopsis Research and Training for the 21 st Century" (ART‐21) Research Coordination Network has been to convene a series of workshops with community members to explore issues concerning research and training in plant biology, including the role that research using Arabidopsis thaliana can play in addressing those issues. A first workshop focused on training needs for bioinformatic and computational approaches in plant biology was held in 2016, and recommendations from that workshop have been published (Friesner et al., Plant Physiology, 175, 2017, 1499). In this white paper, we provide a summary of the discussions and insights arising from the second ART‐21 workshop. The second workshop focused on experimental aspects of omics data acquisition and analysis and involved a broad spectrum of participants from academics and industry, ranging from graduate students through post‐doctorates, early career and established investigators. Our hope is that this article will inspire beginning and established scientists, corporations, and funding agencies to pursue directions in research and training identified by this workshop, capitalizing on the reference species Arabidopsis thaliana and other valuable plant systems.